Transactions on Data Hiding and Multimedia Security V - Shi, Yun Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication, and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval, and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. This issue contains a special section on forensic image analysis for crime prevention including two papers. The additional four papers deal with collusion-resistant fingerprinting systems, phase correlation based image matching in scrambled domain, and visual cryptography.
Forensic Image Analysis for Crime Prevention -- Partial Palmprint Matching Using Invariant Local Minutiae Descriptors -- Color Based Tracing in Real-Life Surveillance Data -- Regular Papers -- Collusion-Resistant Fingerprinting Systems: Review and Recent Results -- Phase-Only Correlation Based Matching in Scrambled Domain for Preventing Illegal Matching -- A Comprehensive Study of Visual Cryptography -- Secure Masks for Visual Cryptography.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Optical pattern recognition; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Algorithm Analysis and Problem Complexity; Computers and Society; Pattern Recognition